In het teken van de kunst, X manieren van tekenen in hedendaagse kunst. - Damme, C.van (Gent : Academia press, 1997)
Hyber, Fabrice ; Bourgeois, Louise ; Rouan, François ; Raysse, Martial ; Alberola, Jean-Michel ; Messager, Annette ; Vandeghinste, Inez ; Swennen, Walter ; Oppenheim, Dennis ; Nash, David ; Kracht, Yvonne ; Raveel, Roger ; Maeyer, Marcel ; Panamarenko ; Mandelbaum, Stéphane ; Van Kerckhoven, Anne-Mie ; Costantini, Luca ; Darboven, Hanne ; Bilquin, Jean ; Dierickx, Karel
boek